(NwOKAL_NOE ISKUSSTWOs (NU^EBNOE POSOBIE(B. (NNOTY(B.s - (Ns(B.(N|(B.(NdELLE(B.s; (Nn(B.(Na(B.(NaLEKSANDRROWAs (NPEREWOD^IKs ((NsANKT(B-(NpETERBURGs (NlAN_s (NpLANETA mUZYKIs, 2024)
(N|NRIKO dELLE sEDIE (B1822-1907)-(NITAL_QNSKIJ OPERNYJ PEWEC (B((NBARITON(B), (NPREDSTAWITEL_ ITAL_QNSKOJ [KOLY BEL_KANTO(B,(NWYDA@]IJ PEDAGOG(B,(NPROFESSOR pARIVSKOJ KONSERWATORII(B.s